2018 28th International Symposium on Discharges and Electrical Insulation in Vacuum (ISDEIV) 2018
DOI: 10.1109/deiv.2018.8537129
|View full text |Cite
|
Sign up to set email alerts
|

System Design of Fast Actuator for Vacuum Interrupter in DC Applications

Abstract: One of the major challenges of DC circuit breakers is the required fast mechanical actuator. In this paper, a Thomson coil actuator system for a vacuum interrupter is designed. Active damping is used to decelerate the moving contacts. Challenges are discussed, especially concerning the power supply needed for the Thomson coil actuator. The design philosophy is explained and FEM simulation results are presented. The results indicate that a wide range of combinations of drive circuit capacitance and voltage fulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
3
1
Order By: Relevance
“…The opening and closing time of the VI will be 3.5 ms and 4 ms, respectively. The values deviate from the ones reported in [38] due to minor design changes. To interrupt, current injection is started after an interruption delay of 2 ms which can be shorter than the The results from an interruption capability test are shown in Fig.…”
Section: Resultscontrasting
confidence: 87%
See 1 more Smart Citation
“…The opening and closing time of the VI will be 3.5 ms and 4 ms, respectively. The values deviate from the ones reported in [38] due to minor design changes. To interrupt, current injection is started after an interruption delay of 2 ms which can be shorter than the The results from an interruption capability test are shown in Fig.…”
Section: Resultscontrasting
confidence: 87%
“…This interface enables communicating with the control system of the DCCB. The relevant parameters have been extracted from simulations of a prototype VI actuator system [38]. The opening and closing time of the VI will be 3.5 ms and 4 ms, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The authors showed that the second excitation is inefficient because the increasing contact gap reduces the electromagnetic coupling of the excited TC and the armature. Active damping of the TCA used in this work was already studied with finite element simulations for DCCB application [15]. The authors concluded that the requirements on the TCA system, specifically the DC power supply, are stringent and that active damping works only for a narrow parameter range.…”
Section: Introductionmentioning
confidence: 88%
“…The eddy currents induced in the armature cause a repelling magnetic field that, in this case, decelerates the armature. Active damping has to be perfectly timed for proper deceleration as studied in [15]. Otherwise, the armature may hit the opposing TC with high impact and damage it.…”
Section: B Thomson-coil Actuatormentioning
confidence: 99%